2015
DOI: 10.1038/nmat4276
|View full text |Cite
|
Sign up to set email alerts
|

Quasiparticle-mediated spin Hall effect in a superconductor

Abstract: In some materials the competition between superconductivity and magnetism brings about a variety of unique phenomena such as the coexistence of superconductivity and magnetism in heavy-fermion superconductors or spin-triplet supercurrent in ferromagnetic Josephson junctions. Recent observations of spin-charge separation in a lateral spin valve with a superconductor evidence that these remarkable properties are applicable to spintronics, although there are still few works exploring this possibility. Here, we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
111
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(123 citation statements)
references
References 29 publications
6
111
2
1
Order By: Relevance
“…As reported in an s -wave superconductor NbN 3 , thermally-excited quasiparticles can produce ISHE voltage in the superconducting state, although further experimental verification in other s -wave superconductors seems necessary 1 . In our case, however, ISHE mediated by quasiparticles does not explain the oscillations, since the YBCO length along the voltage contacts is much greater than the charge imbalance length, the length scale where the spin-polarized quasiparticle currents relax into the Cooper-pair condensates 3 . Also, the quasiparticle scenario does not explain the presence of the onset temperature of the oscillations (~30 K), which is much lower than T C .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…As reported in an s -wave superconductor NbN 3 , thermally-excited quasiparticles can produce ISHE voltage in the superconducting state, although further experimental verification in other s -wave superconductors seems necessary 1 . In our case, however, ISHE mediated by quasiparticles does not explain the oscillations, since the YBCO length along the voltage contacts is much greater than the charge imbalance length, the length scale where the spin-polarized quasiparticle currents relax into the Cooper-pair condensates 3 . Also, the quasiparticle scenario does not explain the presence of the onset temperature of the oscillations (~30 K), which is much lower than T C .…”
Section: Resultsmentioning
confidence: 95%
“…The singlet-triplet conversion of paring amplitudes at the interfaces offers tantalizing possibilities for superconducting spintronics devices in which Joule heating and dissipation are minimized 2 . Also, it was recently reported that thermally-excited quasiparticles, superpositions of electron-like and hole-like excitation with spin-1/2, exhibit a giant spin Hall effect by electric spin injection into an s -wave superconductor NbN 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The fact that there is a giant enhancement in the spin Hall angle for quasiparticles with energies around the gap is consistent with the main findings of Refs. [25,26]. We provide microscopic expressions for the density of states in the superconductor with respect to its normal-state value N S ( ) and the scattering times in Eq.…”
Section: -3mentioning
confidence: 99%
“…Moreover, these studies indicated that the magnitudes of the skew scattering and the side-jump contributions are renormalized by different amounts below the superconducting critical temperature in spin Hall devices. Recent nonlocal measurements found an inverse spin Hall signal that is 2000 times stronger in the superconducting state compared to the normal state [26].…”
Section: Introductionmentioning
confidence: 99%
“…Refs. [30][31][32][33][34][35] considered out-of-equilibrium situations, in which quasiparticle effects give rise to spin (charge) currents as a result of charge (spin) injection. In particular, Ref.…”
Section: Introductionmentioning
confidence: 99%